(untitled) (Contemporary Mathematics, 2020)
Using the normalization of the fractional Laplacian (-△)su(x) over the space Ck(Rn ) for all s > 0 and s ≠ 1, 2, ···, we evaluate (-△)se-||x||2 based on the multidimensional surface integrals over the unit sphere and special functions.